0767 Analysis Of The Effect On Blood Pressure And Heart Rate When Adding Solriamfetol (Sunosi) To Stimulant Therapy. (27th May 2020) - Meskill, G J; Meskill, S D
Abstract: Introduction: Solriamfetol is a non-stimulant wakefulness-promoting agent (WPA) indicated for the treatment of excessive daytime sleepiness in adult patients with obstructive sleep apnea or narcolepsy. It acts by inhibiting reuptake of dopamine and norepinephrine. Since many patients with excessive daytime sleepiness take stimulants, clinicians commonly ponder the safety of adding solriamfetol in this population due to concern of increased blood pressure and/or heart rate (HR). Methods: We conducted a retrospective chart review and identified 18 patients who had solriamfetol added to their stimulant therapy. Of those, 7 to date have had a follow-up appointment after the addition of solriamfetol (6 on 150mg, 1 on 75mg). We collected the blood pressure and HR readings at the appointment immediately prior to and following the addition of solriamfetol and conducted a paired t-test. Results: The systolic blood pressure (SBP) had a mean difference of -0.57 (95% CI -9.6 to 8.5, p=0.88), diastolic blood pressure (DBP) 1.7 (95% CI -4.4 to 7.9, p=0.52), mean arterial pressure (MAP) 0.95 (95% CI -5.6 to 7.5, p=0.73), and HR 6.6 (95% CI -0.07 to 13.2, p=0.052). Conclusion: The addition of solriamfetol to stimulant therapy did not lead to a significant increase in SBP, DBP, MAP, or HR. Support: none